4(x+2)=14+-2(3+4x)

Simple and best practice solution for 4(x+2)=14+-2(3+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=14+-2(3+4x) equation:


Simplifying
4(x + 2) = 14 + -2(3 + 4x)

Reorder the terms:
4(2 + x) = 14 + -2(3 + 4x)
(2 * 4 + x * 4) = 14 + -2(3 + 4x)
(8 + 4x) = 14 + -2(3 + 4x)
8 + 4x = 14 + (3 * -2 + 4x * -2)
8 + 4x = 14 + (-6 + -8x)

Combine like terms: 14 + -6 = 8
8 + 4x = 8 + -8x

Add '-8' to each side of the equation.
8 + -8 + 4x = 8 + -8 + -8x

Combine like terms: 8 + -8 = 0
0 + 4x = 8 + -8 + -8x
4x = 8 + -8 + -8x

Combine like terms: 8 + -8 = 0
4x = 0 + -8x
4x = -8x

Solving
4x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
4x + 8x = -8x + 8x

Combine like terms: 4x + 8x = 12x
12x = -8x + 8x

Combine like terms: -8x + 8x = 0
12x = 0

Divide each side by '12'.
x = 0

Simplifying
x = 0

See similar equations:

| -2(6-3x)=-12+6x | | 2m^2+15m+25=0 | | -5d=19 | | 4a-5=29-3 | | 4(9x+2)-5(3+4x)=0 | | -6+k=18 | | 14x-48=x^2 | | 6(x-3)+10=6x-8 | | 3/2-6+5/2=4t+2 | | 3x+5=7+3x-9 | | 5+1.5(z+2)=3.5z-6 | | 2r^2-r-5.25=0 | | 6+-3(6)= | | b^2+8b=-16 | | 475x+25=725 | | 3x+5=7+3y-9 | | b^2+8b=16 | | W-12=-4 | | 5x(2x-1)(5x+7)=0 | | b-6=-3 | | 5n(n+2)=10 | | 8(4-2x)=12-16x | | 2(2x-3)-5(1x+1)=x-4 | | a(a-9)(a-8)=0 | | 6(2q-1)=2q+8q | | N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 | | (a+9)(a+2)=0 | | p+0.06p=148.4 | | n*5+3-10=30 |

Equations solver categories